HAMBATAN KOMUNIKASI INTERAKSIONAL PADA DPAC PDIP DI KECAMATAN BATU AJI KOTA BATAM - Muarif, Dwi Safitri Rahmadani (SCIENTIA JOURNAL, 2023)
Indonesia is a country that uses a democratic system, so political communication is one of the main keys to theestablishment of politics in this democratic country. Communication can be in the form of conveying informationto the public by political party candidates to convey their goals to become a politician. Political communication isalso intended as a vessel for channeling people's aspirations to prospective political members who will advanceas power holders in a democratic country like Indonesia. Therefore the purpose of this study is to find out howthe communication barriers that occur in the Batu Aji sub-district community are carried out by the IndonesianDemocratic Party of Struggle and to find out what causes the delay in the political communication process. Thisstudy used descriptive research with qualitative research methods located in Batu Aji District. Data collectiontechniques used were observation and interview techniques and continued with documentation. The results ofthe discussion obtained are that the success achieved by political actors depends on how political communicationgoes well and smoothly without any obstacles, by building relationships with the community and building trust sothat there is no miscommunication that occurs in politics